1999
DOI: 10.1039/a903380g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and spin relaxation of tempone in a host crystal. An ENDOR, high field EPR and electron spin echo study

Abstract: We studied in the temperature range 4-300 K the dynamics and the electron spin echo decay of the radical 4-oxo-2,2,6,6,-tetramethyl-1-piperidinyloxyl (tempone) doping substitutionally a single crystal of the diketone 2,2,4,4-tetramethyl-cyclobutan-1,3-dione. Electron nuclear double resonance (ENDOR) and high field electron paramagnetic resonance (EPR) spectra (110 GHz) displayed three types of motion: interconversion between twisted-crossover conformations, rotation of the methyl groups and libration of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
52
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 26 publications
9
52
0
Order By: Relevance
“…It is consistent with several recent studies that a nanochannel is useful for slowing down the tumbling motions of molecules in solution within mesopores (6,22). The spectra of the two cryogenic temperatures (i.e., 70 and 50 K) were observed to be greater in the linewidth of each peak than those for 275 and 200 K. At lower temperatures, the rotation of the ring methyl groups of the spin label is slow, relative to the electron-proton hyperfine interactions (23,24). As a result, the ring methyl groups contribute inequivalently to the unpaired electron, resulting in the linewidth broadening of individual peaks.…”
supporting
confidence: 74%
“…It is consistent with several recent studies that a nanochannel is useful for slowing down the tumbling motions of molecules in solution within mesopores (6,22). The spectra of the two cryogenic temperatures (i.e., 70 and 50 K) were observed to be greater in the linewidth of each peak than those for 275 and 200 K. At lower temperatures, the rotation of the ring methyl groups of the spin label is slow, relative to the electron-proton hyperfine interactions (23,24). As a result, the ring methyl groups contribute inequivalently to the unpaired electron, resulting in the linewidth broadening of individual peaks.…”
supporting
confidence: 74%
“…(18) is shown in figure 5. 22 In the fi gure one can see two ESE spectra at different temperatures for a nitroxide radical doping a single crystal. Both Vit) and Vn,(t) change with the temperature.…”
Section: 22mentioning
confidence: 98%
“…The strong impact of hydrogen bonding between the dopant molecule and ethanol host on the spin relaxation was observed in ethanol glass whereas in crystalline ethanol both paramagnetic guest molecules behaved similarly. DOI: 10.1103/PhysRevB.80.052201 PACS number͑s͒: 61.43.Fs, 76.30.Ϫv, 63.50.Ϫx, 65.60.ϩa Coupling of the electron spin to disorder modes of various doped matrices has been extensively studied due to the sensitivity of the approach toward dynamical properties of the observed systems.1-3 Research on disordered solids has shown that nitroxyl radicals can contribute toward the characterization of glass-forming materials, 4-6 providing experimental data for the development of self-consistent theories of molecular dynamics in glasses in general.7-10 The work presented here has been in part motivated by the lack of nitroxyl spin-lattice relaxation-time data measured below 20 K in disordered solids 11,12 and, to the best of the authors' knowledge, by the very few examples comparing paramagnetic relaxation rate data in glassy and crystalline states of the same compound. 13 Solid ethanol has been found to be a very convenient model system for the investigation of molecular solids, as it can be easily prepared in phases characterized by different types of disorder.…”
mentioning
confidence: 99%
“…[1][2][3] Research on disordered solids has shown that nitroxyl radicals can contribute toward the characterization of glass-forming materials, [4][5][6] providing experimental data for the development of self-consistent theories of molecular dynamics in glasses in general. [7][8][9][10] The work presented here has been in part motivated by the lack of nitroxyl spin-lattice relaxation-time data measured below 20 K in disordered solids 11,12 and, to the best of the authors' knowledge, by the very few examples comparing paramagnetic relaxation rate data in glassy and crystalline states of the same compound. 13 Solid ethanol has been found to be a very convenient model system for the investigation of molecular solids, as it can be easily prepared in phases characterized by different types of disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation